2018
DOI: 10.3813/aaa.919245
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Speech Intelligibility Based on Across-Frequency Contrast in Simulated Auditory-Nerve Fluctuations

Abstract: Summary The present study proposes a modeling approach for predicting speech intelligibility for normal-hearing (NH) and hearing-impaired (HI) listeners in conditions of stationary and fluctuating interferers. The model combines a non-linear model of the auditory periphery with a decision process that is based on the contrast across characteristic frequency (CF) after modulation analysis in the range of the fundamental frequency of speech. Specifically the short-term across-CF correlation between no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…Furthermore, the level analysis showed that sCASP can account for the effects of stimulation level on SI, thus reflecting processing limitations of the system both at low presentation levels (reflecting audibility limitations) and at high presentation levels (reflecting loss of frequency resolution and increased upwards spread of masking). Similar realistic SI predictions at different presentation levels were shown by the models of Scheidiger et al (2018) and Zilany and Bruce (2007). Both approaches included non-linear stages in their auditory preprocessing, indicating that the active mechanisms reflected in the sCASP framework might be responsible for its level-dependent behavior.…”
Section: A Essential Model Components For Si Predictionsupporting
confidence: 63%
See 4 more Smart Citations
“…Furthermore, the level analysis showed that sCASP can account for the effects of stimulation level on SI, thus reflecting processing limitations of the system both at low presentation levels (reflecting audibility limitations) and at high presentation levels (reflecting loss of frequency resolution and increased upwards spread of masking). Similar realistic SI predictions at different presentation levels were shown by the models of Scheidiger et al (2018) and Zilany and Bruce (2007). Both approaches included non-linear stages in their auditory preprocessing, indicating that the active mechanisms reflected in the sCASP framework might be responsible for its level-dependent behavior.…”
Section: A Essential Model Components For Si Predictionsupporting
confidence: 63%
“…The proposed sCASP model performs a crosscorrelation of the modulation-spectrograms of the template and target in its backend by means of an analysis of the relationship across frequency bands including both the time and audio-frequency axes. This approach is similar to the ones proposed in Carney (2018) and Scheidiger et al (2018). Previously, Chabot-Leclerc et al (2014) argued that in the condition of phase-jitter distortion the data could only be accounted for by the sEPSM framework when adding an explicit analysis across audio-frequencies, inspired by the work of Elhilali et al (2003).…”
Section: A Essential Model Components For Si Predictionmentioning
confidence: 82%
See 3 more Smart Citations